Avaliação óptica, ultraestrutural e expressão de proliferação celular da mucosa entérica de frangos de corte suplementados com glutamina e ácido glutâmico - Aguiar, Édina de Fátima [UNESP] (2014)
Two experiments were conducted in the Poultry Section/UNESP/ Botucatu. In the first, to evaluate the performance of broilers, 720 chicks of one day old, male, Cobb® were allocated, in a population density of 12 birds/m². The experimental design was completely randomized with four treatments and six replicates of 30 birds each. In the second, to evaluated intestinal biometrics and integrity of enteric mucosa through optical microscopy, that 340 chicks of one day old male, Cobb® were allocated. The design was completely randomized with four treatments and five replicates of 17 birds each. The treatments were both experiments: 1 - basal ration; 2 - basal ration supplemented with 1% glutamine; 3 - basal ration supplemented with 1% glutamic acid; 4 - basal ration supplemented with 2% of the combination of glutamine and glutamic acid. In experiment I, weight gain, feed intake, feed conversion and viability at end each phase of raising and the IEP at 42 days of age were evaluated. In experiment II, 180 birds were sacrificed, and at each period assessed at seven, fourteen and forty two days only 60 birds were euthanized being collected for the evaluation of enteral biometrics, the intestines of 15 birds per treatment, while for the morphometry of different tunics small intestine, these 60 birds sacrificed by period, five birds per treatment were the small intestine segments, totaling 20 birds per evaluation period listed. In for seven, fourteen and thirty-five days of birds supplemented with synthetic amino period showed better feed conversion when compared to the control group. The enteric biometric was not influenced the treatments. The morphometry of different coats of the intestinal wall was influenced at 7 days of age, and the birds supplemented with 1% glutamic acid was significantly more thicker tunica serosa of the duodenum and jejunum mucosa. However at fourteen and forty two days of age, the treatment did not affect the tunics ...